Malaya quest / Muhamad Nabil Nazhan Mohammad Nazri - Mohammad Nazri, Muhamad Nabil Nazhan (College of Creative Arts, Universiti Teknologi MARA, Kedah, 2024)
This abstract provides an overview of Weyrdworks an award winning game development studio pioneering enterprise established in 2016 by Shawn Beck & JT Yean. Located in Petaling Jaya, Selangor. Weyrdwork has swiftly evolved into a leading entity in gaming development industries in Malaysia. The company's primary focus remains on creating fun games, renowned for their tagline “games are made for gamers, by gamers”. It exemplifies the company's commitment to quality, innovation, and customer satisfaction, cementing Weyrdwork's position as a frontrunner in the market. For my final year project, with their permission to use the company name, I will create a game called Malaya Quest. It is a 2D pixel game that being create to elevate local malay tradition to a new type of platform because there was never a game like this before. The game is a vibrant and culturally rich exploration that invites players to embark on an adventurous odyssey through the diverse landscapes of Malaysia. The issue that I have stumble upon was it difficult to create a clear sense of progression or direction for the player and also the layout and the structure of the game must be carefully consider. As for the solution, the game world must have multiple path and hidden areas to encourage exploration. I will also use authentic audio and visual and create a clear sense of progession. As for the conclusion Malaya Quest narrative to evolution, blending tradition with innovation to establish itself as the first video game about Traditional Malaysia and will attract people outside Malaysia to play and understand Malaysia tradition.